A small mitochondrial double-stranded (ds) RNA element associated with a hypovirulent strain of the chestnut blight fungus and ancestrally related to yeast cytoplasmic T and W dsRNAs. - Polashock, J J (1994)
A small double-stranded (ds) RNA element was isolated from a moderately hypovirulent strain of the chestnut blight fungus Cryphonectria parasitica (Murr.) Barr. from eastern New Jersey. Virulence was somewhat lower in the dsRNA-containing strain than in a virulent dsRNA-free control strain, but colony morphology and sporulation levels were comparable. A library of cDNA clones was constructed, and overlapping clones representing the entire genome were sequenced. The 2728-bp dsRNA was considerably smaller than previously characterized C. parasitica dsRNAs, which are 12-13 kb and ancestrally related to the Potyviridae family of plant viruses. Sequence analysis revealed one large open reading frame, but only if mitochondrial codon usage (UGA = Trp) was invoked. Nuclease assays of purified mitochondria confirmed that the dsRNA was localized within mitochondria. Assuming mitochondrial translation, the deduced amino acid sequence had landmarks typical of RNA-dependent RNA polymerases. Alignments of the conserved regions indicate that this dsRNA is more closely related to yeast T and W dsRNAs and single-stranded RNA bacteriophages such as Q beta than to other hypovirulence-associated dsRNAs.